Determining the grades and standard levels of some mental skills as an indicator for the selection of young volleyball players - Setar Mohammed , Khalil; Aed Shamkhi, Doaa; Jabar Mohammed, Mohammed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this study was to determine the grades and standard levels of some mental skills as an indicator for the selection of young volleyball players. The researchers used the descriptive approach with the survey method. The sample was composed of 129 young volleyball players of Iraqi clubs. The researchers identified the scale and procedures and applied it to the research sample. Analyzing the data, it was found that most of the volleyball players of the sample had an average level of mental skills. Considering this, it is highly recommendable to accompany physical training programs with psychological and tactical programs, in order to improve not only physical skills but also mental skills.